THE QASHASH AL-QUR’AN: THE STUDY OF THE PROPHET’S PRAYER IN SURAH AL-ANBIYA 83-84 IN THE PANDEMIC CONTEXT - Hamidi, Ali; Nuryansah, Mohamad (UIN Sayyid Ali Rahmatullah Tulungagung, 2021)
Abstract This paper aims to explain the qashash al-Qur'an about Prophet Ayyub (Job) in his fortitude and patience to face the examination, then take lessons and ibrah for the current social context, where the world community, especially Muslims, is experiencing an examination in the form of the arrival of the Covid 19 outbreak. This paper is the result of the library research with the title